Prediction Model of In-Band Blocking Interference under the Electromagnetic Radiation of Dual-Frequency Continuous Wave - Kai Zhao; Guanghui Wei; Yaping Wang; Xiaodong Pan (International Journal of Antennas and Propagation)
Two hypotheses for the blocking effect mechanisms under the electromagnetic radiation are presented, and the corresponding dual-frequency interference prediction models are proposed, which can be used to predict the working state of equipment under the condition that the single-frequency susceptibility is known. By taking a radar and a communication radio as the EUT, the experiments of dual-frequency continuous wave electromagnetic radiation are designed and carried out to verify the prediction models. The test results show that the sensitive bandwidth of blocking interference effect for the tested radar and the communication station is consistent with their working bandwidth, respectively. By substituting the test data into the proposed prediction models, the prediction errors of the models are less than 13%. Moreover, it can be found that the tested radar is more sensitive to the peak value of electric field, and the tested communication station is more sensitive to the effective value of electric field.